2016
DOI: 10.1016/j.juro.2016.02.1216
|View full text |Cite
|
Sign up to set email alerts
|

Mp65-05 Polyacrylamide Hydrogel (Bulkamid®) in the Treatment of Female Stress Urinary Incontinence: Three Year Follow Up Outcomes.

Abstract: METHODS: ISD was created in female NHPs by cutting and then cauterizing the pudendal innervation to the urinary sphincter complex. Chronic fibrotic, muscle poor ISD developed within 6 months post-surgery. Partial bone marrow transplantation with autologous Lenti-GFP bone marrow cells (BMCs) was performed and NHPs (n¼6/ experimental condition) were then given sphincter injections of Lenti-Mcherry-labeled 5 million autologous skMPCs, or SDF-1a. Tissues were removed 6 months later and analyzed for sphincter conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Three studies present shorter follow-up data of standard PAHG injection with a timeline similar to our study 20,21,23 . However, comparison continues to be limited by differing definitions of subjective and objective outcomes, methods of data collection, and varying sample sizes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Three studies present shorter follow-up data of standard PAHG injection with a timeline similar to our study 20,21,23 . However, comparison continues to be limited by differing definitions of subjective and objective outcomes, methods of data collection, and varying sample sizes.…”
Section: Discussionmentioning
confidence: 78%
“…However, comparison continues to be limited by differing definitions of subjective and objective outcomes, methods of data collection, and varying sample sizes. Pai et al 23 offer a retrospective study of 212 women and report 82.8% subjective improvement (defined as subjective cure or significant improvement) at 3-month follow, which was stable over the 5-year study. Umberto et al 21 demonstrated a 1-month subjective success rate of 89.1%, which declined to 59.7% at 3 months, 72% at 6 months, and 74.4% at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…22 Currently no migration of the material has been reported at 2 years follow-up 23,24 ; however, pain and erosion were reported at 25 months in one study. 25 Pai and Al-Singary 13 referenced Bulkamid as nonmigratory and non-degradable even after 10 years as it has previously been used in breast surgery and as a soft tissue filler in plastic surgery. In a case report, Bulkamid was shown to form a periurethral abscess causing pain 6 weeks post-injection 26 ; similarly, Zuidex has been shown to cause a paraurethral abscess.…”
Section: Isolated Case Reports and Reviews Of Long-term Complicationsmentioning
confidence: 99%
“…Pai and Al-Singary 13 followed up 256 patients injected with Bulkamid for a minimum of 3 years, with a median follow-up of 38 months. Only short-term complications affecting seven patients were described, with 18 patients undergoing a second injection to achieve desired symptomatic control.…”
Section: Introductionmentioning
confidence: 99%